(untitled) (Al-Qamar, 2025)
This research study examines the foundational principles of tafakkur (reflection) and tadabbur (deep contemplation) in the interpretation of the Holy Qur’an, emphasizing their essential role in achieving a balanced, authentic, and methodologically sound understanding of the divine text. While the Qur’an repeatedly urges believers to reflect upon its verses, this study argues that such contemplation is neither unrestricted nor purely subjective; rather, it must operate within a well-defined scholarly framework rooted in the Qur’an itself, the Sunnah of the Prophet ﷺ, the understanding of the Companions, Arabic linguistics, context, and established principles of tafsīr. The article critically analyzes contemporary trends that either excessively restrict Qur’anic reflection to specialists alone or, conversely, promote unregulated personal interpretations detached from classical methodology. By surveying classical and modern scholarly approaches, the study clarifies the legitimate scope, limits, and objectives of reflective interpretation, highlighting the dangers of intellectual deviation arising from non-principled exegesis. Ultimately, the research demonstrates that disciplined tafakkur and tadabbur are indispensable for preserving the Qur’an’s theological integrity, intellectual coherence, and practical guidance, while ensuring that interpretation remains aligned with the objectives of divine revelation and the welfare of the Muslim Ummah.